2020
DOI: 10.46364/njmlm.v8i2.436
|View full text |Cite
|
Sign up to set email alerts
|

In-service teacher attitudes toward the use of the mother tongue in Norwegian EFL classrooms

Abstract: Because of the lack of research on the use of the mother tongue (MT) in the English as a foreign language (EFL) classroom in European contexts, and because the topic is rarely discussed in teacher training programs, teachers often assume that students prefer an environment that makes little to no use of their MT. What complicates matters further is that while policy makers suggest maximal use of the target language (TL), European curricula for English as a subject do not contain any direct statements prescribi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Despite the growing academic consensus that confirms the important role of the L1 in foreign language instruction, exclusive use of the TL is still regarded as good practice and a commonsense approach by many teacher educators and policymakers (Butzkamm & Lynch, 2018;Kerr, 2016;Neokleous & Ofte, 2020). Furthermore, actual language use has been found to vary greatly across classrooms in different educational contexts, even in settings where exclusive TL use is prescribed (Inbar-Lourie, 2010;Littlewood & Yu, 2011;Rabbidge & Chappell, 2014;Shin et al, 2020).…”
Section: Language Use In Practicementioning
confidence: 99%
See 3 more Smart Citations
“…Despite the growing academic consensus that confirms the important role of the L1 in foreign language instruction, exclusive use of the TL is still regarded as good practice and a commonsense approach by many teacher educators and policymakers (Butzkamm & Lynch, 2018;Kerr, 2016;Neokleous & Ofte, 2020). Furthermore, actual language use has been found to vary greatly across classrooms in different educational contexts, even in settings where exclusive TL use is prescribed (Inbar-Lourie, 2010;Littlewood & Yu, 2011;Rabbidge & Chappell, 2014;Shin et al, 2020).…”
Section: Language Use In Practicementioning
confidence: 99%
“…As most Scandinavian primary teachers of English are generalists and share an L1 with their learners, they are at a strategic and pedagogical advantage, as this increases their repertoire of skills and tools for teaching (Copland & Yonetsugi, 2016). Monolingual classrooms are uncommon and as in other contexts, language use has been found to vary greatly across classrooms, in all three countries (Cadierno et al, 2020;Krulatz et al, 2016;Neokleous & Ofte, 2020;Schröter & Molander Danielsson, 2016). In Norway, Krulatz et al (2016) found that a majority of primary teachers reported TL use of between 15% and 75%.…”
Section: English In Scandinaviamentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, as even recent research indicated, Norwegian was the language that prevailed in Norwegian EAL classrooms and Greek in Cypriot EAL classrooms (Neokleous and Ofte, 2020;Armostis and 10.3389/feduc.2023.1254025 Frontiers in Education 03 frontiersin.org Tsagari, 2022) as teachers worked in linguistically homogeneous classrooms (Lorenz et al, 2021). The teachers often resorted to using the majority language to exemplify and clarify queries, answer questions, and provide instructions.…”
Section: Introductionmentioning
confidence: 99%